2019
DOI: 10.1111/his.13882
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1, B7‐H3 and VISTA are highly expressed in gestational trophoblastic neoplasia

Abstract: Aims: The B7 family check-point molecules are potential therapeutic targets in cancer immunotherapy. However, their expression status in human gestational trophoblastic neoplasia (GTN) remains unknown. We investigated the expression profiles of the B7 family check-point proteins PD-L1, PD-L2, B7-H3, B7-H4, VISTA and B7-H6 in GTN and their clinical significance. Methods and results: We identified 112 patients with GTN, including 68 with choriocarcinoma, 33 with placental-site trophoblastic tumour (PSTT) and 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 30 publications
3
43
0
Order By: Relevance
“…Expression of PD-L1, B7-H3, B7-H4, and VISTA in CCC of the Cervix. Consistent with our previous study [13,14], the patterns of PD-L1, B7-H3, B7-H4, and VISTA staining in cervical CCC were predominantly membranous; representative images are shown Figure 1. PD-L1 was expressed in both TCs and TAICs and was positive in 11 samples (22%).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Expression of PD-L1, B7-H3, B7-H4, and VISTA in CCC of the Cervix. Consistent with our previous study [13,14], the patterns of PD-L1, B7-H3, B7-H4, and VISTA staining in cervical CCC were predominantly membranous; representative images are shown Figure 1. PD-L1 was expressed in both TCs and TAICs and was positive in 11 samples (22%).…”
supporting
confidence: 90%
“…Immunohistochemistry (IHC) was performed using our laboratory protocol as described previously [13,14]. Briefly, 4 μm series of whole tissue sections were deparaffinized and subjected to heat-induced epitope retrieval with 10 mM sodium citrate (pH 6.0) at 95°C for 20 minutes.…”
Section: Immunohistochemistry and Evaluationmentioning
confidence: 99%
“…Using real-time polymerase chain reaction, Lines et al found that VISTA was predominantly expressed in human placental and hematopoietic tissues, as well as in tissues that exhibit markedly high leukocyte infiltration [28]. We also found that normal human organs other than lymphoid tissues and placental trophoblastic cells did not express VISTA at the protein level [13]. Although VISTA protein has been detected in gastric cancer, oral squamous cell carcinoma, NSCLC, colorectal carcinoma, hepatocellular carcinoma, endometrial cancer, ovarian cancer, melanoma, and gestational trophoblastic neoplasia, its expression and relationship with patient survival vary according to the type of cancer [13][14][15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 53%
“…Human tonsil and placenta tissues that were obtained from the Department of Pathology, Peking Union Medical College Hospital, Beijing, China, were used as positive controls, whereas normal tonsil tissues without primary antibodies were used as negative controls. Immunohistochemistry was performed using our laboratory protocol as described previously [13,22].…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation